2021
DOI: 10.1038/s41586-021-03669-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota regulate social behaviour via stress response neurons in the brain

Abstract: Social interactions among animals mediate essential behaviours, including mating, nurturing, and defence 1,2 . The gut microbiota contribute to social activity in mice 3,4 , but the gut-brain connections that regulate this complex behaviour and its underlying neural basis are unclear 5,6 . Here we show that the microbiome modulates neuronal activity in specific brain regions of male mice to regulate canonical stress responses and social behaviours. Social deviation in germ-free and antibiotic-treated mice is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(151 citation statements)
references
References 48 publications
8
142
1
Order By: Relevance
“…Enterococcus is a Gram-positive opportunistic pathogen that could cause pneumonia and bacteremia in patients with stroke, worsening functional outcome (20). Mechanically, Enterococcus was reported to have interactions with platelets (27) and could modulate neuronal circuits that mediate stress responses (28). It is noteworthy that the pathogenic bacterium Desulfovibrionaceae, previously reported to be elevated in patients with stroke and associated with stroke severity (9), showed a decrease in the unfavorable outcome group in this study, which gives rise to the complicated patterns of microbial dysbiosis influenced by the stroke that worth further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus is a Gram-positive opportunistic pathogen that could cause pneumonia and bacteremia in patients with stroke, worsening functional outcome (20). Mechanically, Enterococcus was reported to have interactions with platelets (27) and could modulate neuronal circuits that mediate stress responses (28). It is noteworthy that the pathogenic bacterium Desulfovibrionaceae, previously reported to be elevated in patients with stroke and associated with stroke severity (9), showed a decrease in the unfavorable outcome group in this study, which gives rise to the complicated patterns of microbial dysbiosis influenced by the stroke that worth further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests an involvement of the MGB axis in the modulation of the host's stress response. In Sudo et al's landmark study, germ-free mice showed an enhanced secretion of plasma ACTH and corticosterone, when compared with specificpathogen-free (SPF) mice, under restraint stress [10], and it was later shown that modulation of the gut microbiota could affect the stress response, including the HPA axis [24,25]. Meanwhile, numerous studies, both animal and human, have been performed on the role of probiotics in stress resilience [26][27][28][29][30].…”
Section: Abnormal Stress Responsementioning
confidence: 99%
“…Depleted microbiota is associated with increased hippocampal noradrenaline and reduced serotonin levels ( de Palma et al, 2015 ; Hoban et al, 2016 ), increased neuronal activation in areas associated with stress response, such as the paraventricular nucleus of the hypothalamus (PVN) and bed nucleus of the stria terminalis (BNST) ( Wu et al, 2021 ), and decreased gene expression of glucocorticoid receptors and CHF in the hippocampus and amygdala ( Hoban et al, 2016 ). Likewise, mice with depleted microbiota have increased basal corticosterone levels and HPA reactivity in response to acute stress, which can be reversed by microbiota recolonization ( Clarke et al, 2013 ; Wu et al, 2021 ). Moreover, chronic probiotic treatment reduces the corticosterone reactivity to acute stress and improves depressive phenotype ( Bravo et al, 2011 ; Liang et al, 2015 ).…”
Section: The Roles Of Microbiota On Depression Anxiety and Microrna E...mentioning
confidence: 99%
“…Remarkably, GF rodents tend to present reduced anxiety- and depression-like behaviors ( Heijtz et al, 2011 ; Clarke et al, 2013 ; de Palma et al, 2015 ; Wu et al, 2021 ) and are resilient to behavioral impairments induced by maternal separation ( de Palma et al, 2015 ). Such aberrant profile is associated with reduced hippocampal BDNF expression, increased hippocampal and striatal serotonin levels, and plasma tryptophan concentrations ( Heijtz et al, 2011 ; Clarke et al, 2013 ).…”
Section: The Roles Of Microbiota On Depression Anxiety and Microrna E...mentioning
confidence: 99%